The underestimated burden of aspiration event and pneumonia within hospitals: what happens after dysphagia - Lesa, L.; Brunelli, L.; Valent, F.; Aprili, I.; Cametti, E.; Ferrari, S.; Camussi, E.; Degan, S.; De Corti, D.; Bellomo, F.; Tardivo, S.; Siliquini, R.; et al. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. Despite dysphagia large prevalence and the growing ageing phenomenon occurring in European countries, aspiration events among inpatients are often underestimated, given their frequent spontaneous resolution or silent contribution to aspiration syndromes. Our main objective was to evaluate the incidence of aspiration events among medical inpatients and to identify risk factors influencing the outcome of the event. Study design. Prospective observational study. Methods. Data about aspiration events - day, hour, type and outcome of the event occurred – along with underlying patient clinical conditions at the admission were collected. Between May 2015 and September 2016, data about aspiration event occurred among medical inpatients were collected in three large Italian hospitals. Results. Patients affected by aspiration events were 135 on 102,619 cumulative days of hospitalization; they were mostly females (53%) with an average age of 82. The total incidence of aspiration events was of 1.4 every 1,000 days of hospitalization (C.I. 95%: 1.2-1.7) and the most frequent manifestation was cough (61.6%). The addition of drugs or an infection diagnosis during the 24 hours preceding the event acted as risk factors for those events that needed additional interventions during the hospitalization (OR 3.1 e OR 1.9 respectively), while the elimination of one or more prescribed drugs seemed to lead to aspiration events without impact on the hospitalization. Conclusions. Results showed a large incidence of aspiration events within medical wards, many of them influencing patient outcomes. Healthcare professionals’ attention concerning aspiration events should be fostered during the first hours and days of hospitalization.